Youth - a romantic concept? - Oesterle, Günter (Enthalten in:Jugend;Würzburgt : Königshausen & Neumann, 1997;1 Online Ressource (13 Seiten);Seite 31-43, 1997)
Research has contended youth is an
urn:nbn:de:hebis:30:3-633482